Bioassay Guided Fractionation Identified Hederagenin as a Major Cytotoxic Agent from Cyclocarya paliurus Leaves - Gao, Ying; He, Chunnian; Bi, Wu; Wu, Guofan; Altman, Elliot (Planta Medica, 2016)
An ethanol extract prepared from the leaves of Cyclocarya paliurus, also known as sweet tea, which is one of the most popular teas utilized in traditional Chinese medicine, exhibited significant cytotoxicity against human lung and breast cancer cells. Using a bioassay-guided fractionation, we purified a pentacyclic triterpenoid, hederagenin, which exhibited superior and selective cytotoxicity against human breast and lung cancer cells. Evaluation of the structure-activity relationship between hederagenin and seven other pentacyclic triterpenoids revealed that the C3 hydroxyl group, the C17 carboxyl group and the Δ12,13 double bond could be important active groups for the bioactivity of pentacyclic triterpenoids, whereas introduction of a hydroxyl group at C2 or C23 might reduce their bioactivity. We also investigated the cytotoxic activity of hedeargenin and demonstrated that it induces apoptosis, increases the cell membrane permeability, reduces the mitochondria potential, and suppresses NF-κB activation.
Keywords: Cyclocarya paliurus; Juglandaceae; hederagenin; pentacyclic triterpenoids; cytotoxicity; NF-κB activation